ضمان الخسارة في الفقه الإسلامي - سيلا، محمد الأمين محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This is a fundamental study on the jurisprudential basis of guarantee of losses. The study aims at propounding a solution to the existing lacuna on issues of guarantee in contemporary financial transactions as it also explains the Shariah ruling on stipulating guarantee of losses on one of the contractual included parties, and the ruling on third party guarantee. The methodology used by the researcher inductive and analytical approaches which made the comparison. This came after shedding light on the concept of sharikah, its types in Islamic jurisprudence as well as giving detailed explanation of sharikah al-'inan. The study also discusses the importance of using Musharakah mutanaqisah as an offshoot of sharikah al-'inan, explains the concept of guarantee, the general ruling that is connected to it, and some Islamic legal maxims. Similarly, the study looks at the concept of loss and its economic and non-economic causes. The researcher further elucidates that guarantee contains protection of rights of one of the parties from getting lost and the permissibility of taking guarantee in gratuitous contract. But it is not permissible to stipulate guarantee in the contractual agreement. However, with regards to third party guarantee the researcher highlights the preference to its permissibility. This is because he is not privy to the contract. This type of guarantee is righteous, encouraged and mutually assisting in reforming the situation of investment.